Has the Gratuité policy reduced inequities in geographic access to antenatal care in Burkina Faso? Evidence from facility-based data from 2014 to 2022 - Offosse, Marie-Jeanne; Yameogo, Pierre; Ouedraogo, André Lin; Traoré, Zanga; Banke-Thomas, Aduragbemi (Frontiers in Global Women's Health, 2024)
Background Evidence shows that user fee exemption policies improve the use of maternal, newborn, and child health (MNCH) services. However, addressing the cost of care is only one barrier to accessing MNCH services. Poor geographic accessibility relating to distance is another. Our objective in this study was to assess the effect of a user fee exemption policy in Burkina Faso (Gratuité) on antenatal care (ANC) use, considering distance to health facilities. Methods We conducted a cross-sectional study with sub-analysis by intervention period to compare utilization of ANC services (outcome of interest) in pregnant women who used the service in the context of the Gratuité user fee exemption policy and those who did not, in Manga district, Burkina Faso. Dependent variables included were socio-demographic characteristics, obstetric history, and distance to the lower-level health facility (known as Centre de Santé et Promotion Sociale) in which care was sort. Univariate, bivariate, and multivariate analyses were performed across the entire population, within those who used ANC before the policy and after its inception. Results For women who used services before the Gratuité policy was introduced, those living 5–9 km were almost twice (OR = 1.94; 95% CI: 1.17–3.21) more likely to have their first ANC visit (ANC1) in the first trimester compared to those living <5 km of the nearest health facility. After the policy was introduced, women living 5–9 km and >10 km from the nearest facility were almost twice (OR = 1.86; 95% CI: 1.14–3.05) and over twice (OR = 2.04; 95% CI: 1.20–3.48) more likely respectively to use ANC1 in the first trimester compared to those living within 5 km of the nearest health facility. Also, women living over 10 km from the nearest facility were 1.29 times (OR = 1.29; 95% CI: 1.00–1.66) more likely to have 4+ ANC than those living less than 5 km from the nearest health facility. Conclusions Insofar as the financial barrier to ANC has been lifted and the geographical barrier reduced for the populations that live farther away from services through the Gratuité policy, then the Burkinabé government must make efforts to sustain the policy and ensure that benefits of the policy reach the targeted and its gains maximized.